Do technical skills correlate with non-technical skills in crisis resource management: a simulation study - Riem, N.; Boet, S.; Bould, M. D.; Tavares, W.; Naik, V. N. (Université d'Ottawa | University of Ottawa, 2012)
Background. Both technical skills (TS) and non-technical skills (NTS) are key to ensuring patient safety in acute care practice and effective crisis management. These skills are often taught and assessed separately. We hypothesized that TS and NTS are not independent of each other, and we aimed to evaluate the relationship between TS and NTS during a simulated intraoperative crisis scenario. Methods. This study was a retrospective analysis of performances from a previously published work. After institutional ethics approval, 50 anaesthesiology residents managed a simulated crisis scenario of an intraoperative cardiac arrest secondary to a malignant arrhythmia. We used a modified Delphi approach to design a TS checklist, specific for the management of a malignant arrhythmia requiring defibrillation. All scenarios were recorded. Each performance was analysed by four independent experts. For each performance, two experts independently rated the technical performance using the TS checklist, and two other experts independently rated NTS using the Anaesthetists’ Non-Technical Skills score. Results. TS and NTS were significantly correlated to each other (r¼0.45, P,0.05). Conclusions. During a simulated 5 min resuscitation requiring crisis resource management, our results indicate that TS and NTS are related to one another. This research provides the basis for future studies evaluating the nature of this relationship, the influence of NTS training on the performance of TS, and to determine whether NTS are generic and transferrable between crises that require different TS
Keywords: cardiopulmonary resuscitation; clinical competence; medical education; patient simulation